The Level of Professional Ambition Among Student's Jordanian Universities and Its Relationship to Some Variables - AL-Momani, Mohammad Omar; Shdaifat, Sameer Aowad Kassab (Journal of Ecohumanism, 2025)
The study aimed to identify the level of professional ambition among Jordanian university students and its relationship to the variables of gender, type of specialization, and type of university. To achieve the objectives of the study, the descriptive approach was used, in addition to using the questionnaire as a tool for the study, which was applied to (6983) male and female students. The study concluded that the level of ambition among the students was (medium) with an arithmetic mean of (3.27), and a standard deviation of (0.62), and the study found that there were statistically significant differences in the level of professional ambition among university students, which were attributed to gender variables, in favor of males, and to the type of academic specialization variable, in favor of students in scientific specializations. The study also found that there are no statistically significant differences in the level of professional ambition among university students, which is attributed to the variable type of university in which the student studies.